The silver linings of lottery play: motivation and subjective well-being of British lottery participants. Issue 18 (11th December 2016) - Burger, M. J.; Hendriks, M.; Pleeging, E.; van der Zwan, P. W.
ABSTRACT: Although certain researchers have attributed widespread lottery play to irrational beliefs that people hold regarding the chances of winning the lottery, another explanation for the popularity of lottery gambling is that lottery players may experience positive emotions before the draw. Therefore, in this study, we examine the relationship between lottery participation and happiness. Using data from the British Gambling Prevalence Survey 2010 and utilizing propensity score matching methods, we find a small positive effect of lottery participation on happiness for individuals who engage in lottery play for recreational purposes.